Fertilización química en el cultivo de arroz (Oriza sativaL.) en época seca en el cantón Naranjito. - Ortega Guevara, Delfin Masdeus (2012)
This research conducted on the property of Luis Ortega, located in the Rcto. Anapoyo canton Naranjito, province of Guayas, whose location is: Latitude South 2, 17 and west longitude 70 °, 25, the duration of the investigation was 6 months in order to 1) analyze the agronomic performance of crop 4.15 rice foliar and soil fertilization under 2.) to analyze the benefit / cost of treatment in studies. To determine the research used 5 treatments and 4 repetitions with a design of randomized complete block (DCA), we studied the different chemical fertilization programs: 1.) Urea 300 Kg/ha-1 2.) 500 ml/ha-1 Green Humic + 500 ml/ha-1 Raizoot + 300 kg/ha-1 of Urea 3.) 300 Kg/ha-1 Urea + 50 kg/ha-1 DAP + 50 Kg/ha-1 of Muriate Potassium 4.) 500 ml/ha-1 Green Humic + 500 ml/ha-1 Raizoot + 300 Kg/ha-1 Urea + 500 gr/ha-1 Quantum 5.) 500 ml/ha-1 Green Humic + 500 ml/ha-1 of Raizoot + 300 kg/ha-1 Urea + 500 gr/ha-1 Quantum + 500 ml/ha-1 Biomax + 500 ml/ha-1 Green K. The agronomic variables studied were as plant height, number of tillers per m2, panicle length, panicle per square meter-day flowering of 1000 seeds weight, physiological maturity, yield, lodging, shattering, grain length. If differences were statistically significant. In the economic evaluation of treatment 500 ml/ha-1 Green Humic + 500 ml/ha-1 Raizoot, 300 kg/ha-1 of Urea + 500 gr/ha-1 Quantum + 500 ml/ha-1 Biomax, + 500 ml/ha-1 Green k reported a greater economic benefit of $ 1615.68, with a total cost of $ 876.48. In the economic evaluation T4 treatment 500 ml/ha-1 Green Humic, + 500 ml/ha-1 Raizoot + 300 kg/ha-1 of urea + 500 gr/ha-1 of Quantum, obtained greater benefit / cost of 2,891% and $ 289,1 better profitability.